Bacterial Keratitis. Part 2. Topical Aspects of Treatment - O. V. Shilovskikh; V. O. Ponomarev; V. N. Kazaykin; K. A. Tkachenko (Oftalʹmologiâ)
Bacterial keratitis (BC) is a threatening condition for the anatomy and function of the eyeball and requires an immediate complex of therapeutic measures. Effective treatment that preserves the anatomical and functional result of the organ of vision, including various non-surgical and surgical methods, is the basis for the treatment of CD. Drug therapy includes, first of all, massive etiotropic therapy, which is usually represented by broad-spectrum antibiotics, antiseptics and anti-inflammatory drugs. These combinations make it possible to competitively influence all links of the pathological process, showing an additive effect. Promising non-surgical means in the fight against bacterial infection of the cornea, in particular with resistant microorganisms, is the use of Quantum dots, Mitomycin C, Matrix metalloproteinases. The most radical surgical methods of treatment are based on therapeutic keratoplasty, the purpose of which is to excise the infectious focus of the cornea and restore its transparency through transplantation of donor corneal tissue, but this method has a number of disadvantages and limitations in its implementation. Autoconjunctival keratoplasty is the oldest method of treatment of progressive corneal ulcers and this method should be considered rather as temporary or preparatory before through keratoplasty, due to the lack of visual functions. The least radical and relevant surgical methods of CD treatment today are the use of Corneal Crosslinking, Microdiathermocoagulation, Cyanoacrylate glue, Amniotic membrane transplantation. The expansion of the arsenal of methods of influencing the microbial process of the cornea and their further study will allow for a quick response in response to the rapidly developing antibiotic resistance in the world.